Efficacy and safety of intravenous paracetamol in comparison to ibuprofen for the treatment of patent ductus arteriosus in preterm infants: study protocol for a randomized control trial. Issue 1 (December 2016) - Dani, Carlo; Poggi, Chiara; Mosca, Fabio; Schena, Federico; Lista, Gianluca; Ramenghi, Luca; Romagnoli, Costantino; Salvatori, Enrica; Rosignoli, Maria; Lipone, Paola; Comandini, Alessandro
Abstract Background Patent ductus arteriosus (PDA) is one of most common complications in preterm infants. Although ibuprofen represents the first choice for the closure of PDA, this treatment can cause severe gastrointestinal and adverse renal effects and worsen platelet function. The successful closure of the PDA with paracetamol has been recently reported in several preterm infants, and the safety of paracetamol for this use has been suggested by the available data. Methods/design We present the design of a randomized, multicenter, controlled study, whose aim is to assess the effectiveness and safety of intravenous paracetamol in comparison to intravenous ibuprofen for the treatment of PDA in preterm infants. A total of 110 infants born at 25+0 to 31+6 weeks of gestational age will be enrolled and randomized to receive paracetamol or ibuprofen (55 patients per group) starting at 24–72 h of life. The primary endpoint of the study is the comparison of the PDA closing rate observed after a 3-day course with paracetamol or ibuprofen. The secondary endpoints include the closure rate of PDA after the second course of treatment with ibuprofen, the re-opening rate of the PDA, the incidence of surgical ligation, and the occurrence of adverse effects. Discussion The results of this study will provide new information about the possible use of paracetamol in the treatment of PDA. Paracetamol could offer several important therapeutic advantages over current treatment options, and it could become the treatment of choice for the management of PDA, mainly due to its more favorable side effect profile. Trial registration Clinicaltrials.govNCT02422966 . Eudract no. 2013-003883-30.